(untitled) (Pedagogical Horizons, 2017)
The present article describes the various possibilities of acquiring competences in the area of school experiences – the area where students obtain practical experience in the classroom. Special attention is paid to general skills. Furthermore the motives for pursuing teaching qualification studies are investigated. Finally the results of a brief survey about the aforementioned topics among students at the end of their first year at university are presented.